Neutrophil-to-lymphocyte ratio alone may not be a true indicator of the severity of acute pancreatitis - Tanoğlu, Alpaslan; Düzenli, Tolga (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Tanoğlu A, Düzenli T. Neutrophil-to-lymphocyte ratio alone may not be a true indicator of the severity of acute pancreatitis. Turk J Gastroenterol 2019; 30(10): 937.